Therapeutic Outcomes of High Dose-Dexamethasone versus Prednisolone + Azathioprine, Rituximab, Eltrombopag, and Romiplostim Strategies in Persistent, Chronic, Refractory, and Relapsed Immune Thrombocytopenia Patients - Eman Mostafa Hamed; Ahmed R. N. Ibrahim; Mohamed Hussein Meabed; Ahmed M. Khalaf; Doaa Mohamed El Demerdash; Marwa O. Elgendy; Haitham Saeed; Heba F. Salem; Hoda Rabea (Pharmaceuticals, 2023)
Background: Primary immune thrombocytopenia (ITP) is an inflammatory autoimmune disease that can be managed with several treatment options. However, there is a lack of comparative data on the efficacy of these options in different phases of the disease. Aim of the study: This study aimed to evaluate the efficacy of high-dose Dexamethasone (HD-DXM), Prednisolone + Azathioprine, Rituximab, Eltrombopag, and Romiplostim schedules in persistent, chronic refractory or relapsed Egyptian ITP patients with a platelet count ≤30 × 109/L. The primary outcome measure was a sustained increase in platelet counts over 50 × 109/L for an additional 12 months without additional ITP regimens. The study also aimed to identify a suitable treatment regimen with a long remission duration for each phase of ITP. Results: Prednisolone + Azathioprine was significantly more effective in achieving an overall response in persistent patients than Romiplostim, high-dose Dexamethasone, and Rituximab. (90.9% vs. 66.6, [Odds ratio, OR: 5; confidence interval, CI 95% (0.866–28.86)], 45%, [OR: 0.082, CI 95% (0.015–0.448)] and, 25%, [OR: 30, CI 95% (4.24–211.8)], respectively, p-value < 0.01). Eltrombopag was significantly more effective in achieving a durable response in refractory ITP than HD-DXM, Rituximab, and Prednisolone; (80% compared to 32.2% [OR: 0.119, CI 95% (0.035–0.410)], 22.2% [OR:0.071, CI 95% (0.011–0.455)], and 18.1% [OR: 0.056, CI 95% (0.009–0.342)], respectively, p-value < 0.01). Conclusions: Finally, Eltrombopag following HD-DXM showed the highest percentage of patients with complete treatment-free survival times of at least 330 days. These findings could help clinicians choose the most appropriate treatment for their patients with ITP based on the phase of the disease. This trial is registered in clinicaltrials.gov with registration number NCT05861297.